The Impact of Internet Finance on Bank Profitability. Evidence from The Chinese Commercial Banks - Apostolos Dasilas; Goran Karanovic (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- Does internet finance, measured by P2P lending and third-party payment, affect bank profitability? Motivation- Prior studies have focused on the adoption, development, determinants, acceptance, risks and customer satisfaction using data from developed markets, while the impact of internet finance on bank profitability remains understudied. Our study aims to fill this research gap by investigating the impact of internet finance on the profitability of Chinese banks. Idea- Employing static panel data regression analysis and this study explores whether internet finance, measured by P2P lending and third-party payment, affects bank profitability. Data- We use data from 51 Chinese listed commercial banks during the period 2012-2019. Data were culled from CSMAR database and iResearch website. Findings- The results show that internet finance exerts a positive effect on bank profitability for state-owned and joint-stock commercial banks, but adversely affects the profitability of regional commercial banks Contribution- This is the first study that investigates the effect of internet finance on the profitability of state-owned, joint-stock and regional commercial banks separately. In addition to bank-specific variables, this study also considers macroeconomic variables that have been alleged to affect bank profitability.
Keywords: G15; G21; 650; Internet finance; bank profitability; commercial banks